Antioxidant capacity and characterization of gum arabic crude methanol extract and it is fractions by fourier transform infrared (FTIR) and Raman - Elnour, Ahmed; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Musa, Khalid Hamid (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The current study investigated the antioxidant capacity (AC) of crude methanol extract (CME) and the soluble fractions of chloroform (CHF), hexane (HF), acetone (AF) and methanol (MF) of raw Acacia seyal gum (ASG) and commercial Prebio-T (PTC) respectively. The crude extract and the different soluble fractions were analyzed and evaluated for their potential antioxidant activities using Fourier Transform Infrared (FTIR) and Raman Spectroscopy. The findings presented the many comprehensive variation rules of chemical components provided by the spectrum of FTIR. The identification process with the Raman spectra (RS) macroscopic fingerprint characters and FTIR spectroscopies provided the details on gums and their extracts chemical constituents, as well as the comparison of the components differences among the fractions. In addition, the antioxidant activities of the crude extract and its different fractions were also investigated by using cupric reducing antioxidant capacity (CUPRAC) and ferric reducing antioxidant power (FRAP). All the ASG and PTC crude extract and fractions, with an exception of chloroform and hexane, exhibited antioxidant capacities where the highest antioxidant activities observed on CME and MF of PTC based on the results of CUPRAC (888.6±4.57mg TE/100g extract) and FRAP (741.8 ± 5.81mg TE/100g extract) assays. The PTC and ASG methanol fractions (MF) revealed a significantly different (p ≤ 0.05) high antioxidant power values of 599.8 ± 7.5 and 741.8 ± 5.8 mg TE/100 g of fraction extract for FRAP, and same but insignificantly different (p ≥ 0.05) high value of 356.1 ± 2.62 mg TE/100 g of fraction for CUPRAC. The findings showed that methanol crude extraction (CME) were found to be more effective than AF fractions in the all mentioned assays. Furthermore, the total yield of CME and all the fractions were also determined. The results on the total yield of CME and all other soluble fractions indicated that the acetone fraction (AF) content was significantly higher compared to methanol fraction (MF) for PTC. Based on this study, the antioxidant activities of CME and its rich fractions could be considered as very promising and beneficial for using Acacia seyal gum in food processing, medicine and pharmaceutical industries. Additionally, the lower antioxidant capacity of other fractions might suggest the lack of bioactive compound(s) of chloroform and hexane fractions. However, further work will demonstrate the capability of integrating soluble methanol (crude/fractions) phytochemicals from Acacia seyal gum as an appropriate solvent for the improvement of the extraction techniques of bioactive compounds.